Rigor index, fillet yield and proximate composition of cultured striped catfish (Pangasianodon hypophthalmus) for its suitability in processing industries in Bangladesh - Salma Noor-E Islami; Md. Shaheed Reza; Md. Abul Mansur; Md. Ismail Hossain; Fatema Hoque Shikha; Md. Kamal (Journal of Fisheries, 2014)
Rigor-index in market-size striped catfish (Pangasianodon hypophthalmus, locally called Thai-Pangas) was determined to assess fillet yield for production of value-added products. In whole fish, rigor started within 1 hr after death under both iced and room temperature conditions while rigor-index reached a maximum of 72.23% within 8 hr and 85.5% within 5 hr at room temperature and iced condition, respectively, which was fully relaxed after 22 hr under both storage conditions. Post-mortem muscle pH decreased to 6.8 after 2 hr, 6.2 after 8 hr and sharp increase to 6.9 after 9 hr. There was a positive correlation between rigor progress and pH shift in fish fillets. Hand filleting was done post-rigor and fillet yield experiment showed 50.4±2.1% fillet, 8.0±0.2% viscera, 8.0±1.3% skin and 32.0±3.2% carcass could be obtained from Thai-Pangas. Proximate composition analysis of four regions of Thai-Pangas viz., head region, middle region, tail region and viscera revealed moisture 78.36%, 81.14%, 81.45% and 57.33%; protein 15.83%, 15.97%, 16.14% and 17.20%; lipid 4.61%, 1.82%, 1.32% and 24.31% and ash 1.09%, 0.96%, 0.95% and 0.86%, respectively indicating suitability of Thai-Pangas for production of value-added products such as fish fillets.